Investigating Marital Relationship in Infertility: A Systematic Review of Quantitative Studies - Tao, Peng; Coates, Rosemary; Maycock, Bruce (Infertility, 2012)
Background: Infertility is a complex issue that affects individuals and groups, and also it has serious implications for the mental and social well-being of those involved. The aim of this review was to assess marital relationship in the context of infertility, using data from infertile individuals or both couples. Methods: A literature search was undertaken using multiple databases (Medline, PsycInfo and Scopus) to identify and synthesize all relevant literature published from 1990 to 2011. All studies in the systematic review were confirmed using specific inclusion criteria; the methodological quality of these studies were examined according to a checklist. Results: Of the potential 794 articles, 18 studies were included in the final analysis, of which 6 were graded as high quality and 12 as moderate. The results indicated male factor infertility did not have a negative marital impact. In addition, infertile male participants expressed higher marital satisfaction than their wives. Infertile females had significantly less stable marital relationship compared to fertile females, which was associated with their socio-demographics and treatment experience. For infertile couples, the infertile subjects or their partners’ marital relationship was affected by either member’s infertility, experience specifically coping strategies. Moreover other factors such as sexual satisfaction, age of the infertile couples, education level, and congruency of couples’ perceptions of infertility were associated with the quality of martial relationship.Conclusion: Although the review can provide an outline of marital relationship in infertility, future studies should focus on the perspective from both infertile couple, across a range of different infertility types, including extended sample sizes and longitudinal study designs. In addition, more consideration should be given to qualitative study.